Recollections and Reflections on Organised Sound. - Risset, Jean-Claude (Organised Sound, 2015)
In this contribution to the twentieth anniversary issue of Organised Sound, I first recall the reasons for dedicating a periodical to organised sound which I mentioned in my answer to inquiries from Cambridge University Press before the journal existed. The digital era is still in its infancy and it will permit a host of new ways to organise sound. I suggest in particular the development of an intimate relationship between acoustic and digital sounds; the extension of structural notations of sound and music and their exploitation for novel musical transformation; the amplification of the use of functions and combinations of functions. I evoke some issues discussed in Organised Sound, elaborating in more detail some problematic topics: analysis and reconstruction of computer music, live electronic music performance, perception of musical sound and sensory aesthetics.